2014
DOI: 10.1158/1078-0432.ccr-14-0695
|View full text |Cite
|
Sign up to set email alerts
|

SAR650984, A Novel Humanized CD38-Targeting Antibody, Demonstrates Potent Antitumor Activity in Models of Multiple Myeloma and Other CD38+ Hematologic Malignancies

Abstract: Purpose: The CD38 cell surface antigen is expressed in diverse hematologic malignancies including multiple myeloma, B-cell non-Hodgkin lymphoma (NHL), B-cell chronic lymphocytic leukemia, B-cell acute lymphoblastic leukemia (ALL), and T-cell ALL. Here, we assessed the antitumor activity of the anti-CD38 antibody SAR650984.Experimental Design: Activity of SAR650984 was examined on lymphoma, leukemia and multiple myeloma cell lines, primary multiple myeloma samples, and multiple myeloma xenograft models in immun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
300
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(311 citation statements)
references
References 46 publications
2
300
0
9
Order By: Relevance
“…However, on the Burkitt's lymphoma cell line Ramos we did show caspase-3 activation upon cross-linking of DARA with secondary Ab (8). The homotypic aggregation-related caspase-independent and -dependent PCD was also shown for SAR650984, a chimeric CD38 Ab (40,41), in the absence of secondary cross-linking. Nonetheless, we have previously shown that the direct effect of SAR650984 to induce PCD is comparable to DARA-induced PCD in the presence of a secondary Ab (8).…”
Section: Discussionmentioning
confidence: 68%
“…However, on the Burkitt's lymphoma cell line Ramos we did show caspase-3 activation upon cross-linking of DARA with secondary Ab (8). The homotypic aggregation-related caspase-independent and -dependent PCD was also shown for SAR650984, a chimeric CD38 Ab (40,41), in the absence of secondary cross-linking. Nonetheless, we have previously shown that the direct effect of SAR650984 to induce PCD is comparable to DARA-induced PCD in the presence of a secondary Ab (8).…”
Section: Discussionmentioning
confidence: 68%
“…17 An ongoing phase 1-2 study of daratumumab in combination with lenalidomide and dexamethasone in patients with relapsed myeloma or relapsed and refractory myeloma has shown high response rates and responses that improved over time. 18 SAR650984, a humanized IgG1 monoclonal antibody, also targets CD38, 19 and clinical responses have been reported in patients with relapsed myeloma or relapsed and refractory myeloma who received the drug as monotherapy 20 or in combination with lenalidomide and dexamethasone, findings that further validate this approach. 21 Elotuzumab, a humanized IgG1 monoclonal antibody that targets the signaling lymphocytic activation molecule F7 (SLAMF7), 22 was associated with stable disease as the best response when it was used as a single agent 23 but has shown clinically relevant activity in combination with lenalidomide and dexamethasone in two studies.…”
Section: Discussionmentioning
confidence: 92%
“…12 Macrophages are known to be abundantly present in the bone marrow of MM patients, 4,5 and macrophage-mediated phagocytosis has been demonstrated to be induced by several mAbs targeting MM cells. [13][14][15] The capacity of DARA to induce macrophage-mediated phagocytosis has not been studied thus far.…”
Section: Introductionmentioning
confidence: 99%